Amphotericin B, itraconazole, posaconazole and isavuconazole minimum inhibitory concentration against 85 strains of Rhizopus spp, isolated from the patients having COVID-19 associated mucormycosis in North India - Gupta, Munesh Kumar; Chkravarty, Jaya; Upadhyay, Vaishnavi; Kumar, Bhupendra; Tilak, Ragini (International Journal Of Community Medicine And Public Health, 2024)
Background: Mucormycosis cases are managed by extensive debridement of the affected tissues, with correction of predisposing risk factors and antifungal drugs. Amphotericin B is the drug of choice; however, few azoles also have a good activity against Mucorales. Therefore, the present study was done to determine the minimum inhibitory concentration (MIC) of antifungal drugs against Mucorales, causing COVID-19 associated mucormycosis in North India. Methods: After obtaining written and informed consent, we processed the received tissue, sputum, and gastric lavage samples as per standard mycological procedures. Subsequently, we determined itraconazole, posaconazole, isavuconazole and amphotericin B MIC against the isolated Mucorales (one from each patient) by broth microdilution using CLSIM38A3 guidelines. Results: We received 615 samples from the enrolled 269 patients with CAM. We observed broad aseptate hyphae in 329 fresh tissues, ten sputum and one gastric lavage sample, whereas 163 follow-up excised tissue had broad aseptate hyphae. In addition, 209 Mucorales were isolated with a predominance of Rhizopus arrhizus (n=183), followed by Rhizopus microsporus (n=21) and Rhizopus homothallicus (n=5). We determined MIC against 77 and 8 strains of R. arrhizus and R. microsporus, respectively. Posaconazole had the least MIC. 0.25, 1, 0.5, and 2µg/ml were the MIC50 of posaconazole, amphotericin B, isavuconazole and itraconazole against R. arrhizus strains, respectively, whereas it was 0.125, 0.1875, 0.5 and 2 µg/ml against R. microsporus, respectively. Conclusions: Lower posaconazole MIC makes it a preferred drug for managing the mucormycosis cases; however, availability and cost are the limitations. Thus, amphotericin B and itraconazole may be used in such conditions.